Effect Of Structured Teaching Programme (STP) On Knowledge Regarding Selected First Aid Measures Among School Teachers In Selected Schools, Kamrup (M), Assam.: Life Sciences-Pediatric Nursing - gogoi, Prof. Nirmali; Konwar, Gitumoni; Konjengbam, Bidyashori; Goswami, Anusuya (International Journal of Life Science and Pharma Research, 2022)
“Today’s children are tomorrow’s citizen”. The future pillars of the nation and future of the nation rests on the hands of the children health today. School children being more active and adventuresome, they are prone to falls, sports injury, drowning, vehicle accidents, etc. At this age, children may think they are invincible and that accidents and injuries happen to other people and not to them. First aid is the provision of initial care for an illness or injury. It is usually performed by non-expert, but trained personnel to a sick or injured person until definitive medical treatment can be accessed. It is important to know First Aid so that you can be a help to yourself or others that may be injured. Every school establishment shall have as a minimum one member of staff who is a trained first aider and two emergency first aiders in the work place. In our study Pre-experimental one group pre-test post-test research design and quantitative evaluative research approach was undertaken among school teachers in Radiant International School and Rajdhani Public School, Sonapur, Kamrup (M), Assam. The sample consisted of 62 school teachers and convenience sampling technique was adopted to select the samples. The tools used for data collection was demographic proforma and structured knowledge questionnaire regarding selected first aid measures. The objective of the study is to assess the effect of structured teaching programme (STP) on knowledge regarding selected first aid measures among school teachers. The results showed that there was marked increase in post-test knowledge. In knowledge,the mean post-test knowledge score (22.76) was higher than the mean pre-test knowledge score (13.35) and mean difference between the pre-test and post-test score was 9.41. The calculated ‘t-value’ was 4.10 and p value was 0.000062 at 0.05 level of significance. This indicates that the structured teaching programme regarding selected first aid measures was effective in improving the knowledge of school teachers. The present study concluded that structured teaching programme (STP) regarding selected first aid measures has an effect in enhancing the knowledge among school teachers. Hence, the structured teaching programme can be utilized by school teachers to provide first aid measures in emergency situation and prevent its complication among school children.